Penerapan Model Pembelajaran Relating, Experiencing, Applying, Cooperating, Transferring (REACT) untuk Meningkatkan Pemahaman Konsep Fisika SMA - Iqbal Sugita; Y R Liana; A F Lestari; Ani Rusilowati; Bambang Subali (Physics Education Research Journal, 2020)
The aims of this study was to test the effectiveness of the Relating, Experiencing, Applying, Cooperating, Transferring (REACT) learning model in improving students' understanding of physics concepts. This research used Action Research with the research subjects of class X MIPA 4 SMA N 2 Batang. Data collection techniques using tests. The results of the research in cycle I showed the number of students who got a score of ≥ 60 was 4 students and cycle II was 14 students. These results indicate that the REACT learning model can improve students' understanding of physics concepts. The learning process that is carried out is always connected with events that occur in real life so that students understand the concept more deeply. The REACT learning model can be applied to other physics materials so that students are more actively involved in learning and improve students' understanding of physics concepts.